KRISHNA ESTUARINE COMPLEX WITH REFERENCE TO ITS SHRIMP AND PRAWN FISHERY - Ravindranath, K (Indian Journal of Fisheries, 2011)
The physiography of the lower reaches of river Krishna and the adjoiningcoast is described. Annual variation in salinity, temperature and dissolved oxygenof the coastal waters at one station is presented. A brief account of the fishingcraft and gear, and a list of the 47 species of shrimps and prawns recorded fromthe area are given.